Beyond "Good Governance": The Multi-level Politics of Health Insurance for the Poor in Indonesia. (November 2016) - Fossati, Diego
Highlights: I study free health insurance programs in Indonesian districts and provinces. Intergovernmental cooperation improves policy outcomes at the local level. The effect is significant regardless of baseline levels of healthcare provision. I discuss the implications for the literature on decentralization and development. Summary: Recent decentralization reforms in low- and middle-income countries have revived a long-standing debate on the benefits and drawbacks of empowering local governments. While some scholars highlight advances in local democratic accountability, others emphasize the dangers of decentralized governance when democratic practices are poorly institutionalized. This paper studies the case of health politics in Indonesian local government to contend that the focus on democratic accountability and good governance may be insufficient to explain major policy outcomes associated with decentralization. I show that the quality of local democracy affects health insurance policy during the first stages of the decentralization process. However, to understand policy trajectories over a longer time frame, relations between politicians at different levels of government become the crucial factor. Using original qualitative and quantitative data from nearly 400 Indonesian districts and provinces, I find that regions in which cooperation between provincial and district authorities has emerged display systematically higher levels of health insurance coverage. I explain why multi-level cooperation improves local policy outcomes, and I show that the positive effect of cooperation does not depend exclusively on patronage networks. These findings contribute to the literature on decentralization and development by showing that policy cooperation across levels of government is crucial for the implementation of complex social policies, and that multi-level cooperation can have beneficial effects even when local democratic institutions are weak.